Coronary artery stents in the treatment of ischaemic heart disease: a rapid and systematic review. - Meads, C; Cummins, C; Jolly, K; Stevens, A; Burls, A; Hyde, C (2000)
BACKGROUND: Coronary artery stents are prosthetic linings inserted into coronary arteries via a catheter to widen the artery and increase blood flow to ischaemic heart muscle. They are used in the treatment of ischaemic heart disease (IHD). IHD is a major cause of morbidity and mortality (123,000 deaths per annum) in the UK and a major cost to the NHS. Clinical effects of IHD include subacute manifestations (stable and unstable angina) and acute manifestations (particularly myocardial infarction [MI]). Treatment includes attention to risk factors, drug therapy, percutaneous invasive interventions (PCIs) (including percutaneous transluminal coronary angioplasty [PTCA] and stents) and coronary artery bypass graft surgery (CABG). In the last decade there has been a steady and significant increase in the rate of PCIs for IHD. In the UK, rates per million population increased from 174 in 1991 to 437 in 1998. Stents are now used in about 70% of PCIs. Data from the rest of Europe suggest there is potential for PCI and stent rates to increase considerably. In the UK there is evidence of under-provision and inequity of access to revascularisation procedures. OBJECTIVES: The following questions were addressed. 1. What are the effects and effectiveness of elective stent insertion versus PTCA in subacute IHD, particularly stable angina and unstable angina? 2. What are the effects and effectiveness of elective stent insertion versus CABG in subacute IHD, particularly stable angina and unstable angina? 3. What are the effects and effectiveness of elective stent insertion versus PTCA in acute MI (AMI)? 4. What are best estimates of UK cost for elective stent insertion, PTCA and CABG in the circumstances of review questions 1 to 3? 5. What are best estimates of cost-effectiveness and cost-utility for elective stent insertion relative to PTCA or CABG in the circumstances of review questions 1 to 3? METHODS: A systematic review addressing the objectives was undertaken. DATA SOURCES: A search was made for RCTs comparing stents (inserted during a PTCA procedure) with PTCA alone or with CABG in any manifestation of IHD. The search strategy covered the period from 1990 to November 1999 and included searches of electronic databases (MEDLINE, EMBASE, BIDS ISI, The Cochrane Library), Internet sites, and hand-searches of cardiology conference abstracts and 1999 issues of cardiology journals. Lead researchers and local clinical experts were contacted. Manufacturers' submissions to the National Institute for Clinical Excellence were searched. The search strategy was expanded to look for relevant economic analyses and information to inform the economic model (including searching MEDLINE, the NHS Economic Evaluation Database and the Database of Abstracts of Reviews of Effectiveness). Searches focused on research that reported costs and quality of life data associated with IHD and interventional cardiology. STUDY SELECTION: For the review of clinical effectiveness, inclusion criteria were: (i) RCT design; (ii) study population comprising adults with IHD in native or graft vessels (including patients with subacute IHD or AMI); (iii) procedure involving elective insertion of coronary artery stents; (iv) elective PTCA (including PTCA with provisional stenting) or CABG as comparator; (v) outcomes defined as one or more of: combined event rate (or event-free survival), death, MI, angina, target vessel revascularisation, CABG, repeat PTCA, angiographic outcomes; (vi) trials that had closed and reported results for all or almost all recruited patients. For the economic evaluation, studies of adults with IHD were included if they were of the following types: studies reporting UK costs; comparative economic evaluation combining both costs and outcomes; economic evaluations reporting costs and outcomes separately for the years 1998 and 1999 (to ensure current practice was included).(ABSTRACT TRUNCATED)